EKSPOLITASI ANAK PADA DUNIA ENTERTAIMENT PERIKLANAN - Oktavia, Andrea; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Children are often commercialized in various television and digital media advertisements due to their allure of innocence and high market value. This situation raises legal and ethical issues because the involvement of children often does not consider their basic rights. This study uses a descriptive, normative legal research method, which examines primary and secondary legal materials. Secondary data is analyzed qualitatively. Conclusions are drawn using deductive logic. This study aims to identify forms of child exploitation in the entertainment and advertising sectors, analyze their impacts, and analyze the legal protections children receive. The results indicate that exploitation often occurs in the form of excessive working hours, psychological pressure, and a lack of understanding of children's rights by parents and agencies. Ideal legal protection should be comprehensive, encompassing strengthened regulations, improved oversight mechanisms, strict sanctions for violators, and education and changes in public mindsets. Legal protection for children is not only an obligation of the state but also a collective responsibility of society in creating a more just and humane future for Indonesian children. Keywords: Child Exploitation, Legal Protection, Advertising